The epidemiology of hospital death following pediatric severe community acquired pneumonia - Xiao-Xiao Ao (BMC, 2021)
Abstract Background Community acquired pneumonia is the primary cause of pediatric hospitalizations and deaths in children under 5 years of age. But the epidemiology of death in pediatric severe community acquired pneumonia was not well characterized. Methods This retrospective observational study was performed at the academic Emergency department and intensive care unit and we investigated the timing, cause, mode and attribution of death in children with severe community acquired pneumonia. Results Of 962 subjects with severe community acquired pneumonia, there were 57 non-survivors (5.9% mortality). Median time to death was 7 [IQR 3,16] days from severe community acquired pneumonia recognition. Patients dying ≤7 days were younger, had greater illness severity and higher rate of congenital heart disease, who were more likely to die of a cardiovascular cause. Multiple organ dysfunction syndrome predominated in deaths > 7 days. Unsuccessful cardiopulmonary resuscitation was the most common mode of death at all timepoints. Our findings suggested that in pediatric severe community acquired pneumonia, early deaths were due primarily to cardiovascular dysfunction, while later deaths were more commonly due to multiple organ dysfunction syndrome. Conclusions Deaths from non-pulmonary factors accounted for a substantial portion of non-survivors. Respiratory dysfunction accounted for only a minority of deaths. Our study highlighted limitations associated with rescuing patients with severe pneumonia from death if extrapulmonary organ dysfunctions could not be simultaneously managed.